Bolivia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper on Bolivia reports that it has experienced major increases in its gas reserves, production, and exports. Not only have their levels increased significantly, but also there have been extensive regulatory changes, which range from the privatization of the mid-1990s to the increase in the government's tax take from the hydrocarbons industry. The government has reached new agreements with foreign oil companies that will allow foreign companies to continue recovering part of their old investments.